2022
DOI: 10.1038/s41598-022-26088-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of unrecognized myocardial infarction before elective percutaneous coronary intervention

Abstract: Unrecognized myocardial infarction (UMI) is associated with adverse outcomes. This prospective, single-center study elucidated the prevalence and prognostic significance of UMI before elective percutaneous coronary intervention (PCI) using delayed-enhancement cardiac magnetic resonance (DE-CMR). We enrolled 236 patients with stable coronary artery disease who underwent DE-CMR before elective PCI. The prevalence of UMI and the association of clinical and CMR-derived variables with major adverse cardiac events (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This is a substudy of the prospective study in which protocol was previously reported 10 . Briefly, this study was conducted at Tsuchiura Kyodo General Hospital between May 2017 and April 2020.…”
Section: Methodsmentioning
confidence: 99%
“…This is a substudy of the prospective study in which protocol was previously reported 10 . Briefly, this study was conducted at Tsuchiura Kyodo General Hospital between May 2017 and April 2020.…”
Section: Methodsmentioning
confidence: 99%